2015
DOI: 10.1111/bjdp.12126
|View full text |Cite
|
Sign up to set email alerts
|

Developmental changes in the embodied self of spatial perspective taking

Abstract: Spatial perspective taking consists of mental self-rotation and other cognitive information processing. Mental self-rotation is a process of rotating an embodied representational self through mental simulation of the sensorimotor mechanisms underlying actual self-movement. It was predicted that physical development would affect the operation of the representational self. One hundred and twenty-five individuals aged 5-80 years (57 children, 35 students, and 33 elderly people) executed a video game task of spati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…It seems that explicitly defining the viewpoint by telling them, "Looking from the driver's viewpoint," activated embodied transformation and viewpoint-movement behavior occurred. It is possible that conducting the task while seated on the carpet lowered the burden of body movement or stimulated somatic sensations (Watanabe, 2016) at the time. Furthermore, Kessler and Thomson (2010) demonstrated that response times could be shortened and accurate response rates increased by orienting one's own body in the direction of the viewpoint of the other.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It seems that explicitly defining the viewpoint by telling them, "Looking from the driver's viewpoint," activated embodied transformation and viewpoint-movement behavior occurred. It is possible that conducting the task while seated on the carpet lowered the burden of body movement or stimulated somatic sensations (Watanabe, 2016) at the time. Furthermore, Kessler and Thomson (2010) demonstrated that response times could be shortened and accurate response rates increased by orienting one's own body in the direction of the viewpoint of the other.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been suggested that spontaneous PT2 can be triggered by factors such as another person's eye contact or referential pointing to an object (Zhao et al, 2016). Furthermore, the strength of stimuli producing somatic sensations may affect embodied transformation, as response times become shorter when performing a task standing in an unstable position compared with being seated in a chair (Watanabe, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This method requires that the distance between the participant's head and the eye tracker be kept somewhat constant. In VPT2, the sensation and minute movement of the body is in an unstable position (Watanabe, 2016), and physically turning or moving the body to another viewpoint (Asaoka et al, 2019;Kessler & Thomson, 2010) affects performance. Thus, VPT2 is very sensitive to body sensation and position.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the EB strategy correlates with pretense and imitation abilities and is influenced by body posture and physical competence (Goldman, 2013; Kessler & Thomson, 2010; Watanabe, 2016). Furthermore, EB strategy is associated with emotion recognition and empathetic perspective-taking (Erle & Topolinski, 2015, 2017; Goldman, 2013; Topolinski et al, 2017).…”
Section: Introductionmentioning
confidence: 99%